Penerapan Model Pembelajaran Cooperatif Integratedreading and Composition (CIRC) Terhadap Minat Belajar PAK Siswa Kelas IX SMP NEGERI 3 SITIOTIO Kabupaten Samsosir Tahun Pembelajaran 2023/2024 - Putri Patricia Situmorang; Malani Simanungkalit; Ronny Simatupang (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The research aims to determine whether there is a positive and significant influence from the implementation of the cooperative integrated reading and composition model on the interest in learning PAK of class IX students of SMP Negeri 3 Sitio-tio Samosir Regency for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the application of the cooperative integrated reading and composition model on the interest in learning PAK of class IX students of SMP Negeri 3 Sitio-tio Samosir Regency for the 2023/2024 academic year. This research is a regression research using Descriptive and Inferential Statistics techniques. The population of all students in grades VII-IX of SMP Negeri 3 Sitio-tio for the 2023/2024 academic year who are Protestant Christians is 177 people. Purposive sampling was 33 people. The research instruments were closed questionnaires and observations. The results of the analysis requirements obtained values ​​rcount=0.599>rtabel=0.344 and tcount=4.165>ttable=2.042 indicating a relationship between the cooperative integrated reading and composition model and students' interest in learning PAK and obtained the regression equation. The determination test showed that the magnitude of the influence of the cooperative integrated reading and composition model on interest in studying Christian Religious Education for class IX students at SMP Negeri 3 Sitio-tio for the 2023/2024 academic year was 35.88%. Hypothesis testing obtained Fcount=17.162>Ftable=3.32, so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the cooperative integrated reading and composition model on interest in studying Christian Religious Education of class IX students at SMP Negeri 3 Sitio-tio, Samosir Regency, Academic Year 2023/2024.